2008
DOI: 10.1007/s00705-008-0186-7
|View full text |Cite
|
Sign up to set email alerts
|

EBV and CMV in chronic periodontitis: a prevalence study

Abstract: Periodontitis is an infectious disease involving specific bacteria and viruses. Herpesviruses believed to play roles in it. The present study examines the presence of Epstein-Barr virus (EBV) and cytomegalovirus (CMV) in subgingival and supragingival plaque of 61 patients with chronic periodontitis and 40 healthy controls. A nested polymerase chain reaction method was used. The clinical parameters, clinical attachment level (CAL), probing depth (PD) and bleeding on probing (BOP) were examined. Prevalence of EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 23 publications
5
29
0
2
Order By: Relevance
“…In a few studies, EBV is detected in a healthy oral cavity which is similar to our findings, but with no HCMV detection. 7,18,19 Although few studies showed similar detection rates of HCMV as in our study, there has been a wide and varied report with high levels of viruses to none in certain population with healthy periodontium. 7,9,17,18,[20][21][22][23] In CP, there have been varied reports with some studies finding very high levels of EBV and HCMV.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In a few studies, EBV is detected in a healthy oral cavity which is similar to our findings, but with no HCMV detection. 7,18,19 Although few studies showed similar detection rates of HCMV as in our study, there has been a wide and varied report with high levels of viruses to none in certain population with healthy periodontium. 7,9,17,18,[20][21][22][23] In CP, there have been varied reports with some studies finding very high levels of EBV and HCMV.…”
Section: Discussionsupporting
confidence: 79%
“…7,18,19 Although few studies showed similar detection rates of HCMV as in our study, there has been a wide and varied report with high levels of viruses to none in certain population with healthy periodontium. 7,9,17,18,[20][21][22][23] In CP, there have been varied reports with some studies finding very high levels of EBV and HCMV. 10,18,20,21,23 Our results showed significantly higher levels of both the HCMV and the EBV virus in CP as compared to the healthy periodontium but still was lower than the median range as quoted by Slots 2010.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations